Medical Waste Incineration Ash Waste: Impact On Environmental Health And Its Potential To Be Used For Paving Blocks - Rachmawati, Siti; Syafrudin, Syafrudin; Budiyono, Budiyono (Jurnal Kesehatan Masyarakat, 2023)
ABSTRACT : It is known that medical waste has increased in recent years due to the Covid-19 pandemic, which was followed by an increase in ash from burning medical waste processing using incinerators. The objective of this study is to determine the impact of using medical waste incineration ashes on health and the environment, as well as the potential for using solidification techniques to make the ash into paving blocks. The ash used was obtained from a medical waste processing facility in Surakarta, Indonesia's Central Java. The test object was created using seven different combinations of ash, sand, and cement with a water-cement ration of 0.5 and cured for 28 days. The optimum compressive strength condition was determined as the basis for the composition of medical waste incineration ash as a mixture of paving block raw materials, which was then tested for the content of heavy metal compounds using the SNI 8808: 2019 method. According to research, the ash from medical waste incineration contains heavy metal compounds such as Pb, Ni, Cu, and Cd and has the potential to be used as a mortar mixture. Six of the seven mortar compositions with the addition of incineration medical waste ash met the compressive strength requirements of SNI 03-0691-1996 for category D paving blocks to be used in parks and other places.